Uncertainty Definition on the Constitutive Models for RC Columns Wrapped with FRP - Doran, B.; Erdolen, A.; Akbas, B.; Kutug, Z.; Koksal, H. O. (SPRINGER HEIDELBERG, 2014)
This paper aims to explore the effectiveness of the fiber-reinforced polymer (FRP)-confining mechanism in concrete in which parameters are uncertain. The confinement effect of high stiffness FRP jackets results an increase in the compressive strength of reinforced concrete columns and should be clearly defined. Various constitutive models have been constructed to predict the mechanical behavior of FRP-wrapped columns by considering this effect. However, the mechanical response of confined concrete columns due to FRP jackets under concentric compression has still been a challenging issue, and there are still some uncertainties in mechanical and also geometrical properties in the analysis and design procedure. These uncertainties can be studied with interval analysis (IA) to determine sharp bounds of the mechanical parameters such as effective lateral confining stress, Young's modulus of concrete and FRP, and geometrical parameters. For this purpose, an IA has been performed using deterministic values of compressive strength for significant number (163) of experimental data being reported by several researchers on FRP-confined square/rectangular columns. The results indicate that uncertainties in material parameters and compressive strengths play an important role in determining the lateral stresses of FRP-confined columns.
Keywords: Interval analysis; Uncertainty; Fiber-reinforced polymer; Confining pressure; Reinforced concrete column; REINFORCED-CONCRETE COLUMNS; NON-RANDOM PARAMETERS; STRESS-STRAIN MODEL; CONFINED CONCRETE; JACKETED CONCRETE; NONRANDOM PARAMETERS; RECTANGULAR COLUMNS; INTERVAL-ANALYSIS; STRENGTH; BEHAVIOR; Science & Technology - Other Topics